El barón rampante - Calvino, Italo; Calvo Montoro, María J. (María Josefa); Benítez, Esther; Calvino, Italo (Madrid : Siruela, 2012)
A young, eighteenth-century Italian nobleman defies parental authority by adopting an exclusively arboreal life, watching from his perch in the trees the passing of the Enlightenment and participating in its various delights and duties.
Online resource; title from ePub title page (Digitalia, viewed March 12, 2016)
Keywords: Italy -- Fiction; Historical fiction; Electronic books